2022
DOI: 10.1039/d2cp03990g
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the properties of graphene quantum dots by passivation

Abstract: The electronic and optical properties of graphene quantum dots (GQDs) of size less than 10 nm are different from those of graphene sheets due to quantum confinement effects. For analyzing...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…116 In other recent research, calculations showed that S and B doping can enhance the QY in the NIR region by 26% and 29%, respectively. 103,117 Meanwhile, the mechanism behind GQDs' photoluminescence is not yet fully understood because of their complex electronic band structure, which involves non-radiative transitions. The non-radiative transitions lead to recombination, making the understanding of the PL mechanism challenging.…”
Section: Optical Propertymentioning
confidence: 99%
See 2 more Smart Citations
“…116 In other recent research, calculations showed that S and B doping can enhance the QY in the NIR region by 26% and 29%, respectively. 103,117 Meanwhile, the mechanism behind GQDs' photoluminescence is not yet fully understood because of their complex electronic band structure, which involves non-radiative transitions. The non-radiative transitions lead to recombination, making the understanding of the PL mechanism challenging.…”
Section: Optical Propertymentioning
confidence: 99%
“…161,243 Furthermore, many studies employing DFT calculations model GQDs as monolayer and small-sized structures for the sake of computational convenience when explaining the structure and band gap of GQDs. 244,245 Therefore, the issue of self-assembly of GQDs cannot be ignored, and it is essential to consider methods to mitigate aggregations of GQDs. Two primary strategies are available for this purpose, as follows.…”
Section: Controlling Self-assembly Of Gqdsmentioning
confidence: 99%
See 1 more Smart Citation
“…The uorine has the highest effect among heavy atoms due to the electronwithdrawing capacity of uorine, decreases the energy gap between the HOMO and LUMO, and leads to the shiing of excitation and emission wavelengths towards the red region. [75][76][77][78][79][80] Li et al developed tetraphenyl porphyrin-derived red-emitting carbon dots via a simple solvothermal method using a sulfonation reaction with sulfuric acid. The developed carbon dots were utilized for the bioimaging of HeLa cells.…”
Section: Crucial Aspects For the Synthesis Of Red-emitting Fcnmsmentioning
confidence: 99%
“…One of the new challengers in the carbon family is the graphene quantum dot (GQD), which has a very large bohr excitonic radius and is dependent on the dielectric properties of its surroundings [12,13]. GQDs typically have fascinating properties originating from two-dimensional (2D) graphene along with extraordinary physical and chemical properties of QDs such as quantum confinement effects, desirable band gap depending on size and shape and [14][15][16][17], indicating that they have many possible uses in the optical, electrical, and medicinal sectors.…”
Section: Introductionmentioning
confidence: 99%